Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Volume Perdagangan Terhadap Harga Saham Pada Perusahaan Manufaktur Industri Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021 - Amelia indriyanti Rusmaniar; Immas Nurhayati; Titing Suharti (CV. ITTC INDONESIA, 2023)
This study aims to determine the effect of financial performance on stock prices, in this study the financial performance taken in which the Profitability ratio is Return On Asset (ROA) and solvency ratio is Debt To Equity Ratio (DER) The objects in this study are companies in metal industry manufacturing companies and the like listed on the IDX for the 2016-2021 period. The samples used in this study are purposive sampling methods, namely as many as 9 metal and similar sub-sector companies (PT Indah Aluminium Industry Tbk, Beton Jaya Manunggal Tbk, Saranacentral Bajatama Tbk, Krakatau Steel (Persero) Tbk, Pelangi Indah Canindo Tbk, Gunawan Dianjaya Steel Tbk, Tembaga Mulia Semanan Tbk, Steel Pipe Industry of Indonesia Tbk) listed on the IDX. In conducting this study, several variables were used including independent variables and dependent variables, which are included in the independent variables, namely, Return On Asset Ratio, Debt To Equity Ratio, Ln Asset, Tranding Volume Acivityt whereas, which is included in the dependent variable is Stock Price. Data analysis used simple linear regression analysis and multiple liner regression analysis, correlation coefficient analysis, determination coefficient analysis and t test (partial) and f test (simultaneous). The results of the f test (simultaneous) show that the Return On Asset Ratio, Debt To Equity, Ln Asset, Tranding Volume Acivity does not have a significant effect on the stock price, while partially or t-test each variable Return On Asset does not have a significant effect on the stock price, the Debt To Equity Ratio does not have a significant effect on the stock price, Ln Asset does not have a significant effect on the stock price and the Volume Acivity Tranding does not have an effect against the stock price